(untitled) (Praxis Educativa, 2026)
Contemporary teaching methodologies, in the plural, address theoretical reflection on teaching in a situated, social, historical, and political way; they are seen as poetic and creative, while also contributing to creating privileged spaces for experimentation and the collective construction of knowledge. We present a choral composition that brings together a wide diversity of voices committed to the design of expanded classrooms in and for arts education.